Heart failure in Eastern Veneto: prevalence, hospitalization rate, adherence to guidelines and social costs - Roberto Valle; Renzo Baccichetto; Sabrina Barro; Alessandro Calderan; Emanuele Carbonieri; Maura Chinellato; Mario Chiatto; Alessandra D’Eri; Francesco Corazza; Massimo D’Atri; Raffaela Drigo; Simeone Fabris; et al. (Monaldi Archives for Chest Disease, 2016)
Heart failure is a preminent problem of public health, requiring innovating methods of health services organization. Nevertheless, data are still not available on prevalence, hospitalization rate, adherence to Guidelines and social costs in the general Italian population. The necessity to identifying patients with heart failure derives from the efficacy of new therapeutic interventions in reducing morbidity and mortality. In this study we aimed to identify, in a subset of the Eastern Veneto population, patients with heart failure through a pharmacologic-epidemiologic survey. The study was divided in 5 phases: 1) identification of patients on furosemide in the year 2000 in the ASL 10 of Eastern Veneto general population, through an analysis of a specific pharmaceutic service database; 2) definition of the actual prevalence of heart failure in a casual sample of these patients, through data base belonging to general practitioners, cardiologists, or others. Diagnosis was based on the following criteria: a) previous diagnosis of heart failure; b) previous hospitalization for heart failure; c) clinical evidence, with echocardiographic control in unclear cases; 3) survey of hospitalizations; 4) evaluation of adhesion to guidelines, through both databases and questionnaires; 5) analysis of the social costs of the disease, with a retrospective “bottom up” approach. From a total population of 198.000 subjects, we identyfied 4502 patients on furosemide. In a casual sample of 10.661 subjects we defined a prevalence of heart failure in Eastern Veneto of 1.1%, that rised to 7.1% in octuagenarians. The prescription of life saving drugs was satisfactory, while rather poor was the indication to echocardiography and to cardiologic consultation. Hospitalization rate for DRG 127 was low: 2.1/1000 inhabitants/year in the general polulation and 12.5 /1000 inhabitants/year in patients >70 years of age. Yearly mortality was 10.3%. Social costs were elevated (15.394 €/patient/year), due to a relevant sanitary component (hospital 53%, drugs 28%) and particularly a to an indirect cost component. In conclusion, the assumption of furosemide lends itself as a good marker for identifying patients with heart failure. Patient identification is simple, cheap and cost-efficient, and can be easily reproduced in other regional areas.